Utilization of Mesenchymal Stem Cells in Therapy in the Oral Cavity - Vinna Kurniawati Sugiaman (Universitas Hang Tuah, 2019)
Therapy by using stem cells has recently been considered a scientific breakthrough for the world of medicine and dentistry, and is considered an important weapon in combating various diseases. Mesenchymal stem cells are cells that have the ability to renew themselves, are multipotent, capable of differentiating and proliferating, and are immunosuppressive, so that they can be used to repair and regenerate various tissues through regenerative therapy. The purpose of this paper is to provide a brief overview of various sources of stem cells and the latest findings and also their implications for improving the health of the oral cavity through regeneration of various tissues in the oral cavity. The use of mesenchymal stem cells in the field of dentistry is considered that the new era of dentistry is being started and is expected to change the paradigm in carrying out treatment of diseases in the oral cavity. Mesenchymal stem cells can be isolated from various tissues that can be used in regenerative therapy through tissue engineering to repair and regenerate tissue in the oral cavity. In utilizing this technology, stem cells, regulators, and matrices are needed as a framework that can facilitate cells to cling to, differentiate, proliferate, form matrices, and increase specific interactions between cells. Conclusions, mesenchymal stem cells can be used in regenerative therapy in the oral cavity to repair and regenerate damaged tissue through tissue engineering technology.